TEACHER STRATEGIES IN INSTILLING NATIONALIST VALUES IN THE MILLENNIAL GENERATION IN THE TECHNOLOGICAL ERA - Muhammad Guruh Nuary; Budiman; Mohammad Saro’i; Andika Dirsa; Opan Arifudin (Adisam Publisher, 2024)
Pedagogical competence is very important to build student character, a teacher must have pedagogical expertise. The local wisdom and culture that have developed in Indonesia have been lost to the millennial generation who are currently pursuing formal education. Teachers face difficulties in building students' character, especially nationalism. Teachers fail to understand the characteristics of the millennial generation, including moral and emotional, sociocultural, physical and intellectual aspects, as well as teachers' low interest in reading, which has an impact on students' level of knowledge. To build nationalistic character in the educational process, teachers must be able to master competencies as educators, including pedagogical, professional, social and personal competencies. Apart from that, because what we are facing is the millennial generation who cannot be separated from the world of the internet, teachers must also be able to operate digital- based learning methods and media. In achieving learning goals, especially building nationalistic character in the millennial generation, there are several indicators that need to be considered. This includes teachers having to create learning tools that suit the methods used, these methods having to be varied and digitally based, and students having to actively work together to discuss when given group assignments by their teachers from a collaborative perspective.